Disturbances of Vaginal Microbiome Composition in Human Papillomavirus Infection and Cervical Carcinogenesis: A Qualitative Systematic Review - Wu, Ming; Li, Huanrong; Yu, Hongfei; Yan, Ye; Wang, Chen; Teng, Fei; Fan, Aiping; Xue, Fengxia (Frontiers in Oncology, 2022)
Background: Emerging evidence has demonstrated a close association between perturbations in vaginal microbiota configurations in women and human papillomavirus (HPV) infection, cervical lesions, and cervical cancer (Ca); however, the findings are highly heterogeneous. Aim: To perform a comprehensive systematic review of global disturbance of vaginal microbiota in women with HPV-associated cervical diseases and conduct within- and across-disease comparisons. Method: Twenty-two records were identified in a systematic literature search of PubMed, Web of Science and Embase up to February 28, 2022. We extracted microbial changes at the community level (alpha and beta diversity) as well as taxonomic levels (relative abundance). Within- and across-disease findings on the relative abundance of taxonomic assignments were synthesized qualitatively. Results: Generally, significantly higher alpha diversity was observed for HPV infection, cervical lesions and/or cancer patients than for the controls and significant differences in beta diversity were observed for the overall microbial composition across samples. In the within-disease comparisons, the genera Gardnerella, Megasphaera, Prevotella, Peptostreptococcus and Streptococcus showed the greatest increases with HPV infection; Sneathia and Atopobium showed the inconsistent abundance with HPV infection; and Staphylococcus was observed for Ca. In the across-disease findings, increased levels of Streptococcus and different levels of Gardnerella were shared across HPV infection, high-grade squamous intraepithelial lesions and Ca while Lactobacillus iners varied according to the HPV-related disease subtype. Conclusions: This systematic review shows that vaginal microbiome disturbances are correlated with depletion of Lactobacillus enrichment of anaerobes and increases in aerobic bacteria in HPV infection and related cervical diseases. Moreover, L. iners may exert either protective or pathogenic effects with regard to different states of HPV-related diseases.